Queer Career : Sexuality and Work in Modern America - Canaday, Margot (Book collections on Project MUSE., 2023)
"A masterful history of the LGBT workforce in AmericaWorkplaces have traditionally been viewed as "straight spaces" in which queer people passed. As a result, historians have directed limited attention to the experiences of queer people on the job. Queer Career rectifies this, offering an expansive historical look at sexual minorities in the modern American workforce. Arguing that queer workers were more visible than hidden and, against the backdrop of state aggression, vulnerable to employer exploitation, Margot Canaday positions employment and fear of job loss as central to gay life in postwar America.Rather than finding that many midcentury employers tried to root out gay employees, Canaday sees an early version of "don't ask/don't tell": in all kinds of work, as long as queer workers were discreet, they were valued for the lower wages they could be paid, their contingency, their perceived lack of familial ties, and the ease with which they could be pulled in and pushed out of the labor market. Across the socioeconomic spectrum, they were harbingers of post-Fordist employment regimes we now associate with precarity. While progress was not linear, by century's end some gay workers rejected their former discretion, and some employers eventually offered them protection unattained through law. Pushed by activists at the corporate grassroots, business emerged at the forefront of employment rights for sexual minorities. It did so, at least in part, in response to the way that queer workers aligned with, and even prefigured, the labor system of late capitalism.Queer Career shows how LGBT history helps us understand the recent history of capitalism and labor and rewrites our understanding of the queer past"--